Cadmium Isotope Fractionation and Its Applications in Tracing the Source and Fate of Cadmium in the Soil: A Review - WAN Dan; CHEN Jiubin; ZHANG Ting; AN Yuchen; SHUAI Wangcai (Yankuang ceshi, 2022)
BACKGROUND Soil cadmium pollution has become one of the main factors that endanger human health. Rapid and effective remediation of Cd pollution soil requires a fundamental understanding of Cd sources and geochemical cycling. With the advancement of Cd isotope analysis technology and the in-depth understanding of its fractionation mechanism, Cd isotopes provide new perspectives for understanding the source and fate of Cd in the soil. OBJECTIVES To systematically summarize the cadmium isotope analysis method, and emphasize the research progress, problems, and potential application of Cd isotopes as tracers in soil. METHODS Sample digestion methods, such as high-temperature digestion bombs, microwave acid digestion, ashing, and acid extraction, are reviewed here with ion-exchange separation and multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS). RESULTS Based on previous studies, this review systematically summarizes the fundamental principle and methodology of Cd isotopic analysis methods. For the soil samples, the high-temperature digestion bombs method and microwave acid digestion can meet its cadmium isotope analysis requirements. With sufficient recovery and complete removal of interfering elements, standard-sample bracketing, external normalization, and double-spike techniques can be used for mass bias correction to obtain accurate and reliable Cd isotope data. In addition, the theoretical basis of soil cadmium isotope tracing was reviewed. This review summarizes the cadmium isotopic composition of multiple potential cadmium sources in soil and the direction and extent of cadmium isotope fractionation in typical processes (weathering leaching, adsorption, precipitation/co-precipitation, complexation). Combined with the latest research results, the application of cadmium isotopes in tracing soil cadmium sources and their migration and transformation processes is summarized. CONCLUSIONS In the future, we should further develop and optimize the high-precision cadmium isotope analysis method, construct the fingerprint map of soil cadmium isotope, and reveal the cadmium isotope fractionation mechanisms in the processes of multi-component and multi-interface.